Field experiments on the effects of fire on parasite transmission to amphibian hosts - Nicole Ortega; Alexander Shepack; Wayne Price; Todd Campbell; Kym Rouse Holzwart; Steven A. Johnson; Jason R. Rohr (Ecology, 2025)
The emergence of infectious diseases is often associated with changes to host–pathogen ecology, and wildfires are known to profoundly modify the ecology of terrestrial and freshwater ecosystems. Nevertheless, few studies have employed manipulative experiments to quantify the effects of fire on infections across parasite species. In a mark–recapture study, prescribed burns did not significantly affect the densities of Cuban tree frog (CTF; Osteopilus septentrionalis ) definitive hosts. However, prescribed burn field experiments and a before‐after‐control‐burn mesocosm study revealed that fire decreased a skin‐penetrating nematode in CTFs by killing the parasite's soil‐dwelling, free‐living stage, with hotter fires causing a greater reduction in soil‐dwelling nematodes. Additionally, prescribed burns were associated with increases in a terrestrial acuariid nematode and several aquatic trematode metacercariae in CTFs, likely by increasing intermediate host densities. Seven years after the burns, we found little evidence of full recovery because the trajectories of these parasites did not show clear signs of flattening. These results suggest that fire can have predictable and long‐term direct and indirect positive and negative effects on parasite transmission.

Transcriptomics reveal immune downregulation of newts overwhelmed by chytrid co‐infection - Alexander Shepack; Alessandro Catenazzi (Molecular Ecology, 2020)
What happens when two emergent diseases infect the same host? In a From the Cover article in this issue of Molecular Ecology, McDonald et al. (2020) compare transcriptomic responses to co‐infection by the two chytrid fungi in the skin, liver and spleen of Eastern newts ( Notophthalmus viridescens ). Novel molecular tools, such as high‐throughput DNA sequencing for genome discovery and transcriptomics, have revolutionized our understanding of host–pathogen interactions and disease ecology (Güimil et al. 2005; Rosenblum et al. 2012). For example, epidemiologists are using genomic data to track the spread of the emergent SARS‐CoV‐2 in real time, both locally and globally. RNA sequencing (RNA‐Seq) is routinely employed to study response to disease in humans, improving disease diagnostics, profiling and development of intervention strategies. Transcriptomic profiles may be particularly informative for emergent diseases, whose pathologies and effect on host phenotype are poorly known. Fungal pathogens increasingly threaten a variety of wild and domesticated organisms (Fisher et al. 2012), and two chytrid fungi attacking amphibians are causing one of the worst losses of vertebrate biodiversity ever recorded (Scheele et al. 2019).